2022
DOI: 10.3390/nano12132263
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Thermal Co-Induced Ferromagnetism of Austenite Nanocrystalline FeCoCr Powders for Strong Microwave Absorption

Abstract: Nanocrystalline soft magnetic alloy powders are promising microwave absorbents since they can work at diverse frequencies and are stable in harsh environments. However, when the alloy powders are in austenite phase, they are out of the screen for microwave absorbents due to their paramagnetic nature. In this work, we reported a strategy to enable strong microwave absorption in nanocrystalline austenite FeCoCr powders by deformation-thermal co-induced ferromagnetism via attritor ball milling and subsequent heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Fu et al investigated a way to improve the absorbing performance of nanocrystalline austenite FeCoCr powders via attritor ball milling and subsequent heat treatment. 108 The results showed that the saturation magnetization of the FeCoCr powders increase from 1.43 to 109.92 emu g −1 after ball milling for 4 h. When the heat treatment reached 500 °C, its saturation magnetization exhibited a great increase to 181.58 emu g −1 . Therefore, the strategy improved the material selection of high temperature materials.…”
Section: High Temperature Microwave Absorbing Materialsmentioning
confidence: 92%
“…Fu et al investigated a way to improve the absorbing performance of nanocrystalline austenite FeCoCr powders via attritor ball milling and subsequent heat treatment. 108 The results showed that the saturation magnetization of the FeCoCr powders increase from 1.43 to 109.92 emu g −1 after ball milling for 4 h. When the heat treatment reached 500 °C, its saturation magnetization exhibited a great increase to 181.58 emu g −1 . Therefore, the strategy improved the material selection of high temperature materials.…”
Section: High Temperature Microwave Absorbing Materialsmentioning
confidence: 92%
“…From a kinetic perspective, curvature-driven migration of the grain boundaries accounts for the grain growth [24]. Chemically ordered crystal structures, such as the Fe 3 Si superlattice [25], can inhibit atomic diffusion and, thus, hinder the migration of grain boundaries [26], while their formation in Fe-based alloys is limited to certain elements. The pinning effect has been widely used to stabilize the grains of nanocrystalline particles, such as solute/second-phase dragging [27][28][29].…”
Section: Of 12mentioning
confidence: 99%
“…With the progress in high-power and miniaturized electronic equipment, electromagnetic interference among heated components raises the urgent need for heat-resistant microwave-absorbing materials [1]. Additionally, heat-resistant microwave-absorbing materials are also required to control the radar cross-section (RCS) of hot parts of military devices [1][2][3]. At present, the widely used heat-resistant absorbents, such as silicon carbide [4], carbon-based composites [4,5], and barium titanate ceramics [6], exhibit excellent oxidation resistance and stable phases, while their microwave absorption mainly relies on dielectric loss, and there are difficulties in tuning permittivity dispersion over frequency [7,8], giving rise to narrow-band absorption and large thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, carbon materials generally can work at temperature lower than 400 °C, and the regulation of their permittivity is complex, leading to large thickness and narrow absorption bandwidth. Magnetic metallic absorbents have great potential in preparation of thin-layer, lightweight, wide-band and strong absorbing microwave materials since they possess both dielectric and magnetic loss mechanisms (Magisetty et al, 2018;Fu et al, 2022). However, when they are used at elevated temperature, many challenges appear, such as growth of grain, oxidation and mechanical deterioration when combining with polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%